2024
DOI: 10.1111/srt.13636
|View full text |Cite
|
Sign up to set email alerts
|

Genetic insights into the gut microbiota and risk of facial skin aging: A Mendelian randomization study

Mulan Chen,
Yuhui Che,
Mengsong Liu
et al.

Abstract: BackgroundA growing number of experimental studies have shown an association between the gut microbiota (GM) and facial skin aging. However, the causal relationship between GM and facial skin aging remains unclear to date.MethodsWe conducted a two‐sample Mendelian randomization (MR) analysis to investigate the potential causal relationship between GM and facial skin aging. MR analysis was mainly performed using the inverse‐variance weighting (IVW) method, complemented by the weighted median (MW) method, MR‐Egg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Mendelian randomization (MR) has emerged as a prominent method for examining the potential causative links between various exposures and health outcomes. 6 Differing from traditional observational research, MR analysis uniquely counters reverse causation bias, given that the random allocation of alleles happens prior to the development of diseases. This methodology leverages the random distribution and independent assortment of genetic variations at the time of conception.…”
Section: Introductionmentioning
confidence: 99%
“…Mendelian randomization (MR) has emerged as a prominent method for examining the potential causative links between various exposures and health outcomes. 6 Differing from traditional observational research, MR analysis uniquely counters reverse causation bias, given that the random allocation of alleles happens prior to the development of diseases. This methodology leverages the random distribution and independent assortment of genetic variations at the time of conception.…”
Section: Introductionmentioning
confidence: 99%
“…9 Research has already demonstrated that certain gut microbiota are closely associated with facial skin aging and acne. 10,11 Additionally, studies have shown that inflammatory bowel disease and psoriasis may influence each other through shared genetic mechanisms and tissue expression pathways. 12 However, the relationship between the gut microbiota and the skin microbiota still requires further investigation.…”
mentioning
confidence: 99%